Assessing the Impact of Land-Based Anthropogenic Activities on the Macrobenthic Community in the Intertidal Zones of Anmyeon Island, South Korea - Jian Liang; Hai-Rui Huang; Meng-Yuan Shu; Chae-Woo Ma (Land)
Anthropogenic activities, particularly land reclamation and industrialization, have severely damaged South Korea’s intertidal zones, resulting in a decline in biodiversity. In our study, we assessed the macrobenthic community in the intertidal zone of Anmyeon Island, South Korea, and used remote sensing to evaluate the impact of anthropogenic activities on the adjacent land areas. Spearman and Principal Coordinate Analysis (PCoA) indicated that the remote-sensing ecological index (RSEI) is a viable indicator for assessing the dissimilarity of macrobenthic communities in these zones. Moreover, biota–environment matching (BIO–ENV) and distance-based redundancy analysis (dbRDA) demonstrated that land cover types significantly influence the macrobenthic communities in nearby intertidal zones. Our study suggested that urbanization and agricultural activities have affected the terrestrial ecological environment and the adjacent intertidal communities. Consequently, the protection of these zones should extend beyond their borders to include the management of anthropogenic activities on adjacent lands. Our research contributes valuable insights to help inform conservation strategies and the policy-making necessary to safeguard South Korea’s intertidal zones.